Investigative Study on the Properties of Hollow Concrete Blocks (International Journal of Innovative Research in Computer Science & Technology, 2022)
The utilization of workmanship structures  is as yet broad all through the world. Hollow concrete  blocks have supplanted customary bricks in late  development as a result of the upsides of higher bearing  limit, farmland insurance, and energy protection [1]. The hollow concrete blocks, being lightweight result in a  reduced dead load of the structure [2]. They are practical  and a superior option in contrast to consumed dirt blocks  by their great solidness, imperviousness to fire, have good  thermal protection, less dead burden, and high speed of  development [3]. They are economical in comparison to  the existing building materials. This project includes the  preparation of samples of hollow concrete blocks with the  different number of cavities and different shapes of  cavities (circular and rectangular) using a concrete mix of  1:4:6 and a comparative study is executed concerning brick  masonry and the blocks available in the market. The  strength parameter, economy, lightweight character, and  insulation property are studied and compared. The  compressive qualities of the samples are thought about  after permitting them to solution for 28 days in the curing  tank. The thermal insulation test, block density test, and  water absorption test are also carried out. The results  showed a great deal of insulation from temperature. The  energy consumption of buildings can be reduced to a  significant amount by using these blocks [6]. The  compressive parameters of these samples came to be far  more than those of blocks that are being utilized in the  market. Therefore these types of hollow concrete blocks  can prove to revolutionize the way we design and build our  structures.
Keywords: Hollow Concrete Blocks (HBC); Cavity; Temperature Gradient